Emerging needs and challenges faced in the teaching and training of intellectual property in Malaysia - Abdul Ghani Azmi, Ida Madieha (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Intellectual property plays a vital role in wealth creation and economic development. There are however challenges faced in the teaching and training of intellectual property in Malaysia. The paper discusses the challenges and argues that there is a dire need to teach intellectual property sufficiently, being interdisciplinary in nature, not only to law students but also to non-law students.